PENGARUH LOAN to DEPOSIT RATIO, NON PERFORMING LOAN, DAN DEBT TO EQUITY RATIO DALAM MEMPENGARUHI PROFITABILITAS SEBAGAI VARIABEL INTERVENING TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PERIODE 2022-2024 - Siswanti Siswanti; Ida Subaida; Lita Permata Sari (Fakultas Ekonomi dan Bisnis, 2026)
Banks are institutions operating in the financial services sector and serve as intermediaries between parties with excess funds and those in need of funds. This study aims to examine the effects of the Loan to Deposit Ratio, Non Performing Loans, and Debt to Equity Ratio on Firm Profitability and Value. The research method used in this study is quantitative descriptive. The population in this study is all banking companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The sampling technique used was purposive sampling. Data analysis and hypothesis testing were conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results of direct hypothesis testing using SmartPLS 3.0 indicate that the Loan to Deposit Ratio, Non Performing Loans, and Debt to Equity Ratio have a negative and significant effect on Profitability. Meanwhile, the Loan to Deposit Ratio, Non Performing Loans, and Debt to Equity Ratio have positive but insignificant effects on Firm Value. Profitability has a positive and significant effect on Firm Value. The results of the indirect hypothesis testing indicate that Profitability mediates the significant negative effects of the Loan to Deposit Ratio, Non Performing Loans, and Debt to Equity Ratio on Firm Value.